Description of the larva of Anotogaster klossi Fraser, 1919 (Odonata, Cordulegastroidea, Cordulegastridae), with a note on the known larvae of the genus Anotogaster Selys, 1854 - Keetapithchayakul, Tosaphol Saetung; Kim, Junggon; Lam, Nguyen Ba Vu; Phan, Quoc Toan (Zootaxa, 2025)
The final instar larva of Anotogaster klossi Fraser, 1919 is described and illustrated, based on reared specimens from Vietnam. The larva of A. klossi differs from its congeners in several morphological characteristics, including the manner of ligula, number of premental setae, and the presence of lateral spines on abdominal segments. A comparison with previously described larvae of Anotogaster Selys, 1854 species is provided. This study enhances the understanding of Anotogaster larval morphology and provides valuable insights into taxonomy and biological notes.